A method for estimating the number of collision candidates in two waterways – for all intersection angles. (21st March 2022) - Kaneko, Fujio
Abstract: Estimating the collision frequency of ships ( F ) is important for assessing collision risk on waterways. To date, F has been estimated as the product of the number of collision candidates (N_a ) and the causation probability (P_c) : F = N_a · P_c, where N_a represents the number of collisions that occur when related ships continue on course with no intervention, and P_c is the probability that collision avoidance fails. Fujii developed a general method and Pedersen formulated it to estimate N_a in an intersectional area. Their method is generally called 'the geometric method' because collision candidates are estimated only from the geometric relationship between two ships. The method has been used in many projects to estimate F in waterways; however, its use should be limited to intersection angles ranging from 10° to 170°. This paper presents a method, statistically verified by computer simulation, that can be used at all intersection angles to overcome this limitation. Moreover, it demonstrates strong agreement with Pedersen's method at intersection angles of 10° to 170°.